2014
DOI: 10.1097/jto.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient–Provider Communication Domains with Lung Cancer Treatment

Abstract: Background Patient-physician communication is critical for helping patients understand and complete the complex steps needed to diagnose stage and treat lung cancer. We assessed which domains of patient-physician communication about lung cancer and its treatment are associated with receipt of disease-directed, stage-appropriate treatment. Methods Patients with recently-diagnosed lung cancer were recruited from four medical centers in New York City from 2008 to 2011. Participants were surveyed about discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…This study only evaluated receipt of treatment, but adherence to treatment recommendations may differ between patients with vs. without mental health disorders, which may contribute to the overall survival difference. Finally, mental health disorders may affect interactions and communications between patients and their providers and patient-provider communications has been shown to influence clinical outcomes in lung cancer patients (21, 58, 59)…”
Section: Discussionmentioning
confidence: 99%
“…This study only evaluated receipt of treatment, but adherence to treatment recommendations may differ between patients with vs. without mental health disorders, which may contribute to the overall survival difference. Finally, mental health disorders may affect interactions and communications between patients and their providers and patient-provider communications has been shown to influence clinical outcomes in lung cancer patients (21, 58, 59)…”
Section: Discussionmentioning
confidence: 99%
“…First, we can infer that by carefully listening to and clearly understanding patients’ views, nurses can help bridge the gap between patients’ expectations and the support provided by healthcare professionals, especially regarding active communication. An increasing number of international studies have consistently indicated that communication between patients and healthcare providers is critical for helping patients to express their concerns and report their needs and for adherence to cancer treatment (Schofield et al ., ; Lin et al ., ). In contrast, the lack of active communication might exacerbate patients’ reluctance to express their needs and the nurses’ difficulty in identifying latent issues that could deteriorate patients’ health.…”
Section: Discussionmentioning
confidence: 97%
“…Medical information should be provided in a way that the patient understands the message and accepts the treatment (Lin et al . ; Papadakos et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The way information is provided to the patient must be adapted to the individual patient and their family and they must be given an opportunity to ask questions (Kwok & White 2014;Li et al 2014;Rudolph et al 2015). Medical information should be provided in a way that the patient understands the message and accepts the treatment (Lin et al 2014;Papadakos et al 2014). Both the kind of information and the amount of data that can be provided to a particular person at one time must be considered.…”
Section: Discussionmentioning
confidence: 99%